Sprout: Insights on platform usage and content perception - Simiyu, Maryfaith; Berta Ortiz-Crespo; Muller, Anna (2023)
Sprout is an open-source digital platform developed by MercyCorps. It that makes content available on a range of agricultural topics, from maize and potato value chains, to livestock, financial services, and climate-smart agriculture, which is used by farmer facing organizations to provide advisory to farmers. The Human Centered Design team, as part of Excellence in Agronomy have identified, for the Sprout platform, the different user profiles (referring to the organizations that use advisory Sprout content) and their corresponding journeys while interacting with the platform. Through the understanding of profiles and journeys we have been be able to identify pain points and opportunities for each one of them and to provide tailored recommendations that will increase the usability of the platform.